Finite-time distributed topology design for optimal network resilience - Xue, Dong; Hirche, Sandra (IET control theory & applications, 2019)
The process of enhancing the ability of a complex network against various malicious attacks through link addition/rewiring has been the subject of extensive interest and research. The performance of existing methods often highly depends on full knowledge about the network topology. In this study, the authors devote ourselves to developing new distributed strategies to perform link manipulation sequentially using only local accessible topology information. This strategy is concerned with a matrix-perturbation-based approximation of the network-based optimisation problems and a distributed algorithm to compute eigenvectors and eigenvalues of graph matrices. In addition, the development of a distributed stopping criterion, which provides the desired accuracy on the distributed estimation algorithm, enables us to solve the link-operation problem in a finite-time manner. Finally, all results are illustrated and validated using numerical demonstrations and examples.